10+10x-10=15x-5x+90

Simple and best practice solution for 10+10x-10=15x-5x+90 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10+10x-10=15x-5x+90 equation:


Simplifying
10 + 10x + -10 = 15x + -5x + 90

Reorder the terms:
10 + -10 + 10x = 15x + -5x + 90

Combine like terms: 10 + -10 = 0
0 + 10x = 15x + -5x + 90
10x = 15x + -5x + 90

Reorder the terms:
10x = 90 + 15x + -5x

Combine like terms: 15x + -5x = 10x
10x = 90 + 10x

Add '-10x' to each side of the equation.
10x + -10x = 90 + 10x + -10x

Combine like terms: 10x + -10x = 0
0 = 90 + 10x + -10x

Combine like terms: 10x + -10x = 0
0 = 90 + 0
0 = 90

Solving
0 = 90

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 22/33= | | 2n+3n+11+19=180 | | 6x+5-3x=7(x-1) | | 144=-9(n-10) | | 12(6-2)-1.5=46.5 | | Y=7.75x+22 | | 5x+74=-6 | | 5x+45-24x=-59 | | 0.7(x+100)=0.75x-315 | | 4(8x-3)=14+6x | | 4(p-1)= | | 8y-6y=16 | | -5m+28-5(m-2)=7m-(6m-9)-4m+1 | | 40-2x=-8(7+6x)+4 | | x^2+3x-1.75=0 | | 2.5t-1=3+1.5t | | 4t-6=9-t | | 37-2(x+8)=1 | | -.33x=10 | | -3(x-9)+4/4=-10 | | f(-x)=4x^2+5x+2 | | 46+x=82+64 | | -7p-6(3-2p)=2(p-6)-18 | | z+9= | | P=a-(n-1)b | | 12x+4+2x=3 | | -1-(1+3n)=-(1-10n)-1 | | 3+6+4-2a= | | 651=-93x | | 9-4a=3a+9 | | 3x+-28+3x-30+x=33 | | 0.4=20 |

Equations solver categories